The effectiveness of prolotherapy for recalcitrant medial tibial stress syndrome: a prospective case series. Issue 15 (10th November 2011) - Padhiar, N; Jones, P R; Curtin, M; Malliaras, P; Chan, O; Crisp, T A
Abstract : The aim was to evaluate whether ultrasound-guided injection of 15% dextrose for treatment of recalcitrant medial tibial stress syndrome (MTSS) decreases pain and facilitates a return to desired activity levels. This was a prospective case series. Participants were nine subjects: seven male and two female; (mean age=33.6 years) with MTSS, referred from sports injury clinics across the UK to a specialist centre at a London private hospital, having failed conservative treatment. An ultrasound-guided subperiosteal injection of 15% dextrose was administered by the same clinician (NP) along the length of the symptomatic area. Typically 1 ml of solution was injected per cm of symptomatic area. A second injection was subsequently administered at four weeks for 4 of the 9 subjects. Pain was assessed using a 10 cm visual analogue scale (VAS) at baseline, short-term, medium-term (mean 18 weeks) and at long-term (mean 1 year) follow-up. Symptom resolution and return to activity were measured using a Likert scale at medium-term and long-term follow-up. Subjects reported a significant ( p <0.01) reduction in median VAS pain score at medium-term follow-up compared to baseline. Median improvement per subject was 5/10. At long-term follow-up, median improvement was 4/10. Subjects rated their condition as 'much improved' at medium-term follow-up and 'no change' at long-term follow-up. Median return to sport score at medium-term follow-up was 'returned to desired but not preinjury level' and 'returned to sport at an unsatisfactory level' at long-term follow-up. There were no reported adverse events. Ultrasound-guided 15% dextrose prolotherapy injection has a significant medium-term effect on pain in MTSS. There is a suggestion that this benefit may be maintained long-term. More robust trials are required to validate these findings.